Collette & Laybourn, Eds., Modern Britain Since 1979 - A Reader - von Hartesveldt, Fred (Teaching History: A Journal of Methods, 2005)
Modern Britain since 1979 has many qualities that are desirable in a text, but it also has some limitations and problems. Students will find the text clear and the language accessible. The editors have done an excellent job of tying the information in the various chapters together, so students will come away from reading with an integrated picture of the political history of Britain in the last 25 years. There are chapters concerning feminism and race, but these topics are developed as issues that influenced political change, not as social or cultural phenomena.